A Multilevel Model of Employee Innovation - Wallace, J. Craig; Butts, Marcus M.; Johnson, Paul D.; Stevens, Flannery G.; Smith, Mickey B. (Journal of Management, 2016)
Drawing from tenets of self-determination theory, we propose and test a multilevel model that examines the effects of employee involvement climate on the individual-level process linking employee regulatory focus (promotion and prevention) to innovation via thriving. Using data collected at three points in time from 346 participants in 75 groups, multilevel path analytic results demonstrated support for a positive indirect effect from promotion focus to innovation via thriving and a negative indirect effect from prevention focus to innovation via thriving. In addition, results showed a positive indirect effect from employee involvement climate to innovation via thriving. Perhaps most important, cross-level moderated mediation results demonstrated that employee involvement climate strengthens the relationship between promotion focus and thriving, which, in turn, positively relates to innovation. The theoretical and practical implications of these multilevel effects on innovation are discussed.